Perbandingan: Kualitas Sumber Daya Manusia (SDM) Pariwisata Pra Dan Masa Pandemi Covid-19 di Objek Wisata Pantai Pangandaran - Arga Sutrisna; Ari Arisman (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The purpose of this study was to analyze the comparison of the Quality of Tourism Human Resources in Pangandaran Beach Attraction in the period and before the Covid-19 Pandemic based on emotional intelligence and intellectual intelligence. The method in this research is Comparative Research with a Quantitative approach. The conclusion of this study is that there are Differences in the Quality of Tourism Human Resources in the period and before the covid-19 pandemic in Coastal Attractions based on emotional intelligence and intellectual intelligence, so it can be concluded that there are differences in the Quality of Tourism Human Resources in the period and before the covid-19 pandemic based on Emotional Intelligence (EQ) and Intellectual Intelligence (IQ).